SOSIALISASI DAN PELATIHAN P3K PADA KAWASAN PESISIR - Novita Sari; Adriansyah Arya Pratama, Citra Aulia Amanda, Abdurrozaq Hasibuan (Jurnal Kesehatan, 2024)
The low level of community education in coastal areas is an indication that the community needs training regarding occupational safety and health. So the intensity of population activity has different influences. Dangers that often arise due to people's carelessness include short electrical cables, cigarette smoke, piles of rubbish, lack of knowledge about fire extinguishing systems, and so on. Therefore, this service activity in the form of socialization aims to increase the level of community knowledge. Increase community preparedness and awareness as well as the role of the community in society to know how to interact with the community in dealing with disasters. Knowledge of first aid in emergencies is one of the most important things needed to deal with the possible consequences of an accident or disaster. First Aid in Emergency Situations, respiratory arrest, heavy bleeding, shock, broken bones, etc. It is a set of skills and knowledge in providing first aid to other accident victims, including patients. First aid is important in life management in emergency situations. Lack of competence/skills in providing assistance Firstly, this can be very difficult, especially if management is inadequate and slow. Our approach to mentoring is to communicate and provide tools, training and rewards so that we believe people can gain knowledge and apply it in everyday life.